A longitudinal follow-up study on sustained behavioural change and compliance post BMW management training among healthcare workers - Thakan, Somya; Jain, Mayank; Dhaundiyal, Ankita (International Journal Of Community Medicine And Public Health, 2026)
Background: While training interventions on bio-medical waste (BMW) management have shown immediate improvements in knowledge and practices among healthcare workers, there is limited evidence on the sustainability of such outcomes. This study follows up with the same cohort from the 2022 intervention at three hospitals in Rajasthan to assess long-term behavioural retention and operational compliance six months post-training. Methods: This observational follow-up study included 124 of the original 156 participants. A structured survey and observational audit were conducted to measure retention of knowledge and adherence to BMW segregation protocols, PPE usage, and reporting mechanisms for needle-stick injuries. Spot-checks and supervisor feedback were also recorded. Results: The average knowledge score declined slightly from 16.4 (post-training) to 14.8 after six months but remained significantly higher than the pre-training baseline (9.2, p<0.001). Sustained compliance was observed in 85% for colour-coded segregation, 89% for PPE use, and 82% for hand hygiene. Reporting of needle-stick injuries, however, dropped from 89% to 63%. Class 4 and housekeeping staff showed the most retained improvement, suggesting lasting value in training lower-cadre employees. Conclusions: While slight declines were observed, most key behaviours related to BMW management remained significantly better than baseline. This underscores the value of refresher modules and continuous monitoring to sustain impact. Structured interventions, when coupled with audits and reinforcement, can yield lasting operational changes even in low-resource hospital settings.